Celebrating Psi Chi at Yale University - Harold Takooshian; Florence L Denmark (Peoples' Friendship University of Russia (RUDN University), 2019)
Psi Chi was founded at Yale University on 4 September 1929, during the historic Ninth International Congress of Psychology - the first congress on U.S. soil. This report recounts how Yale University has been partnering with leaders of Psi Chi to host four joyous Anniversary Convocations to date, to salute international psychology, Psi Chi and student excellence in psychology - in 1999, 2004, 2009, and 2019.